Analysis of Structural Second Order Effects on a Floating Concrete Platform for FOWT's. (September 2016) - Campos, A.; Molins, M.; Trubat, P.; Alarcón, D.
Abstract: The irruption of the floating wind energy in the offshore engineering is changing the paradigm of the structural analysis for those new structures, which are significantly smaller and more slender than those previously existing from the O&G industry and in which the most important load is applied around 100m above the mean sea level. Those characteristics require the structural analysis to include the dynamic effects over the deformation of the structure, integrating the instantaneous deformation of the structure into the nonlinear dynamic finite element analysis (FEA) computation. A numerical model which couples the hydrodynamic and aerodynamic effects in a time domain structural analysis, has been developed at the UPC. The code integrates the forces exerted by the waves and currents as well as the aerodynamic loads, including the wind turbine, and the mooring system. For the hydrodynamic loads, Morison's equation in combination with the Stoke's 5th order nonlinear wave theory are used to compute the resulting forces. The mooring system is treated in a quasi-static way and the aerodynamic loads are computed with FAST. The structure is discretized with one-dimensional beam elements, in which the formulation considers small strains as well as large motions. The model computes a dynamic time domain nonlinear FEA for FOWT's, integrating all the effects of the external forces and the structural stiffness to obtain the displacements at each point of the structure at each time step. With this approach, the dynamic interaction between the wind turbine and the structure, as well as the effects on the internal forces are implicitly considered in the formulation. A comparison of the structure motions and internal forces for a concrete spar concept is presented assuming a nonlinear rigid body approach and a nonlinear dynamic time-domain FEA.